A notice of the theory "that there is no hope for a nation which lives on potatoes" - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1849)
The theory "that there is no hope for a nation which lives on potatoes," has been put forward by Sir C. E. Trevelyan, in his recent work, called "The Irish Crisis," as if it were an established doctrine of political economy which no one would venture to controvert. I do not propose to enter into an elaborate refutation of the arguments by which Sir C. E. Trevelyan's theory is usually supported. This has been most ably done by Dr. Longfield, in the note on this subject in his Lectures on Political Economy. But I wish, in the first place, to show that Sir C.E. Trevelyan's theory is not so generally admitted as he seems to suppose, and then to point out the mistakes in which it originated.
Read April 17th 1848
Keywords: Potato famine; C.E. Trevelyan; 314.15